Maqamat Sufistic as a Solution for Coping Stress - Casmini Casmini; Dwiga Aziz Himawan; Hanis Kusuma Wardhani (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2020)
The application and understanding of good coping stress certainly becomes an important thing in the current period. This paper aims to describe the contextualization between coping stress in psychology with maqamat and ahwal in Sufism. Research data was extracted through library research obtained from primary sources in the form of articles and corroborated with coping stress books. Secondary sources are articles in journals that implement Sufi both in Sufi life and in practical implementation of Sufi therapy. The results of the study describe the contextualzation and relationship between maqamat and ahwal in Sufism with coping stress in psychology.